2018
DOI: 10.4102/ojvr.v85i1.1528
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial and temporal distribution of foot-and-mouth disease in four districts situated along the Uganda–Tanzania border: Implications for cross-border efforts in disease control

Abstract: Foot-and-mouth disease (FMD) is one of the major trans-boundary animal diseases in East Africa causing economic loss to farmers and other stakeholders in the livestock industry. Foot-and-mouth disease occurs widely in both Uganda and Tanzania with annual outbreaks recorded. With the recent introduction of the Progressive Control Pathway for FMD control (PCP-FMD) in eastern Africa, knowledge of the spatial and temporal distribution of FMD at the border area between Uganda and Tanzania is helpful in framing enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…A majority (85.31% with p < 0.01, n = 143) of the farmers interviewed reported that FMD is more likely to occur during the major dry seasons (the major one from June to September and a less severe one from December to February) than in the wet season. These months coincide to what was reported by Kerfua et al [16] and the OIE records [14,24]. We found that the majority (102/143 [71.33%]) (p < 0.01) of the farmers practising semi-zero grazing system and fewer (40/ 143[27.97%] practising strict zero grazing.…”
Section: Seasonality Of Fmd Outbreaks and Farming Systemsupporting
confidence: 89%
See 1 more Smart Citation
“…A majority (85.31% with p < 0.01, n = 143) of the farmers interviewed reported that FMD is more likely to occur during the major dry seasons (the major one from June to September and a less severe one from December to February) than in the wet season. These months coincide to what was reported by Kerfua et al [16] and the OIE records [14,24]. We found that the majority (102/143 [71.33%]) (p < 0.01) of the farmers practising semi-zero grazing system and fewer (40/ 143[27.97%] practising strict zero grazing.…”
Section: Seasonality Of Fmd Outbreaks and Farming Systemsupporting
confidence: 89%
“…In this regard, this area has been known to be a hotspot for most of the FMD outbreaks in Rwanda for the last two decades [ 12 ]. The dry season seems to be the period during which FMD outbreaks are more likely to occur in Eastern Rwanda and surrounding areas in Uganda and Tanzania [ 14 – 16 ]. During the dry season, there is a shortage of pasture and water; thereby forcing most livestock farmers to move their animals in search of pasture and water.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in tandem with results from other studies in Uganda by Ayebazibwe et al (2010) and in Tanzania by Allepuz et al (2015), who showed that increased distances from border and from the national park were associated with decreased number of outbreaks in both Uganda and Tanzania. Moreover, Kerfua et al (2018) also showed that sub-counties/wards adjacent to the Uganda-Tanzania border had more outbreaks reported compared to those that were afar off from the border. The results from interviews held with the farmers during the focus group discussions and with the key informants further portrayed the border as important risk factor for FMD occurrence of FMD in Isingiro district.…”
Section: Discussionmentioning
confidence: 95%
“…However, in the region, it comes second alongside serotype A and after serotype O (7,2629). Across the border, in Western Tanzania (Kyerwa and Karagwe districts) and Western Uganda (Isingiro district), SAT 2 has been responsible for several FMD outbreaks (3032). We hypothesize that if these two regions with Eastern Rwanda that make a triangle with transboundary animal movements are not controlled, they can contribute to the circulation of several strains of FMDV and other similar transboundary animal disease pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya, most of the outbreaks have been caused by serotypes O and SAT2 (33). Among the SATs serotypes, SAT2 is the most predominant in East Africa in general (30) and in Rwanda in particular where the last serotype O outbreak was reported in 2004(34). We hereby report the shreds of evidence that SAT2 was responsible for the 2017 and 2020 FMD outbreaks.…”
Section: Discussionmentioning
confidence: 99%